PENGARUH KUPON, SISA UMUR OBLIGASI DAN YIELD TO MATURITY TERHADAP HARGA OBLIGASI KORPORASI DI BEI - Sigalingging, Maria E.; Silalahi, Donalson (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2022)
This study aims to determine and explain the effect of bond coupons, remaining bond life, and yield to maturity on the price of corporate bonds on the Indonesia Stock Exchange. To achieve this goal, a study with a research period of 2017 - 2019 was conducted on 22 companies that issue bonds. By using purposive sampling as a sampling technique, 105 data were observed. The analytical method used is multiple regression analysis. The results showed that the bond coupon variable had a positive and significant effect on bond prices, the remaining life of the bonds had a significant effect on bond prices. The direction of the effect of the remaining life of the bond on the price of the bond depends on the price of the bond, whether the price of the bond is perium or the discount price. Furthermore, yield to maturity has a negative and significant effect on bond prices. The ability of these three variables to explain variations in bond prices is 66.1 percent.